Propuesta de presupuesto estratégico para la empresa megavidrios soluciones integrales para el control de sus actividades segundo semestre de 2022 (2022)
MEGAVIDRIOS SOLUCIONES INTEGRALES S.A.S is a service sector company whose economic activity is the completion and finishing of buildings and civil engineering works, that is, it is dedicated to the supply and installation of architectural structures in glass, steel and aluminum. This sector, which during the declaration of pandemic has decreased its activity, has been maintained thanks to the national government has developed new projects for social housing, relief for new and used housing, as well as interest reduction for the purchase of real estate. The company MEGAVIDIROS SOLUCIONES INTEGRALES S.A.S, has not been indifferent to this dynamic, although strongly affected by the low demand for products and services during 2020. In the case of this work, in addition to delivering a six-month Strategic Budget based on the Results Statements of the Company MEGAVIDRIOS SOLUCIONES INTEGRALES S.A.S, based on the previous 12 months, A projection of the Cash Flow and the Statement of Results of six months will also be made that allows to make constant evaluation of the managerial and operational performance. With the preparation of a Strategic Budget, financial indicators relevant to the accounting area will be chosen with which management will be able to exercise control, determine strategies and improvement plans for the company.